Modulation of Perlecan Protein towards Chondrocyte Secretion Factors at the Articular Cartilage in Hyperglycemic Animal Model - Ibrahim Njoto; Fatchiyah Fatchiyah; Kusworini Handono; Abdurrachman Abdurrachman; Djoko W. Soeatmadji; Handono Kalim (The Journal of Pure and Applied Chemistry Research, 2019)
High carbohydrate influences the cartilage microcellular environment and chondrocytes. Perlecan (HSPG2) conducts an essential role as chondrocytes mechano-transducer and chondrocytes secretion factors. This research aims to fulfill the research gap about hyperglycemia which influences to perlecan of articular cartilage. About twenty male rats were divided into four groups: group I (sugar-treated rats 1.00 mg/kg of BW), group II (sugar-treated rats 1.5 mg/kg of BW), group III (2.00 mg/kg of BW), and control. The Anterior Cruciate Ligament Transection (ACLT) used to generate an unstable joint to be osteoarthritis condition at the right knee. Then, sugar was administrated for two months.  Level expression of the protein was analyzed using Western Blotting. The result showed that perlecan expression was decreased within all sugar-treated rats group as compared to control. The IGF-1 expression was decreased, whereas TGF-β was slightly increased within all treatment groups. Moreover, the expression of FGF-2 was higher in all treatment groups. Of note, IL-1β expression was only elevated in group II and III. The interaction of perlecan to the chondrocyte secretion factors was determined by the cartilage condition within hyperglycemia.